Energy and Ethics - Sovacool, Benjamin K. author. (orcid)0000-0002-4794-9403 Link aut Link
XXII, 278 p.
Keywords: Benjamin K. Sovacool applies concepts from justice and ethics theory to contemporary energy problems, and illustrates particular solutions to those problems with examples and case studies from around the world.